Multiomics genetic insights into potential molecular targets for intracranial aneurysm - Shuo Wang; Xiaolin Chen; Yi Yang; Yitong Jia; Runting Li; Fa Lin (Stroke and Vascular Neurology)
Background This study aimed to identify multiomics therapeutic targets for aneurysmal subarachnoid haemorrhage (aSAH) and unruptured intracranial aneurysm (uIA) using Mendelian randomisation (MR), summary-data-based MR (SMR) and postanalysis methods.Methods Significant genetic variables were extracted from multiple databases, including Expression Quantitative Trait Loci (eQTL) from eQTLGen and Genotype-Tissue Expression V.8, protein QTL from eight plasma studies and methylation QTL from the 2018 genome-wide methylation study. Key molecules linked to aSAH and uIA were identified through MR (SMR) and colocalisation analysis. Functional research and drug development relied on postanalysis approaches, including single-cell analysis, enrichment studies and molecular docking.Results Nine genes and one protein associated with aSAH, along with two genes and one protein for uIA, were identified. DNA methylation variations significantly influenced outcomes. Colocalisation analysis showed most key molecules shared genetic variants with the diseases. The prioritised targets were PSMA4, PRCP, TNFSF12 and RELT. Enrichment and protein–protein interaction studies indicated these proteins acted mainly through the Phosphoinositide 3-kinase-Ak strain transformation (PI3K-Akt) pathway and cytokine interactions. Molecular docking confirmed stable binding of PRCP with benazepril. Single-cell analysis revealed high expression of prioritised targets in inflammatory cells. Phenome-Wide Association Study suggested potential pleiotropy of priority targets.Conclusions The study identified key targets for aSAH and uIA, providing insights for developing preventive therapies and advancing research on intracranial aneurysm mechanisms.